Inter-hospital transport of newborns in critical condition: integrative literature review - Balbino, Aldiânia C.; Cardoso, Maria V. L. M. L.; Silva, Viviane M. da (Medicina (Ribeirao Preto), 2015)
Study model: integrative review. Objective: to identify organizational behaviors described in the literature about inter-hospital transport of newborns in critical health condition performed by means of ambulance. Methodology: integrative review with query in the databases: LILACS, CINAHL, MEDLINE, Web of Science and Scopus, during the period from September to November 2013. In order to perform the research, the non-controlled descriptors ‘newborn transport’, ‘newborn infants’ and ‘protocol’ were used, as well as the controlled descriptors ‘transport of patients’, ‘newborn’ and ‘ambulances’. The search was limited to papers published in Portuguese, English and Spanish, without an established period, which addressed the inter-hospital transport of critically ill newborn by ambulance. Results: 12 papers were selected. The identified behaviors were: pre-transport communication; composition of the team that will conduct the transport; reference and counter-reference; selection of vehicle for transportation; equipment and medications that may be used during transportation. Conclusions: The selected studies address the important measures to be applied at all stages of the inter-hospital transport of newborns by ambulance, which are important for quality and effective care